Contemporary Art at the State Russian Museum: On the Question of the Replenishment of the Collection - Karlova, Anastasia I. (Actual Problems of Theory and History of Art, 2024)
The research is devoted to the problem of the replenishing the collection of contemporary art at the State Russian Museum. The objective was to trace the main stages of the collection’s development from the end of the 19th century (when the museum was founded) until now and to identify the basic features and characteristics of contemporary museum practice in this field. The theoretical understanding of these stages, as presented in the article, allowed to consider the phenomenon of collecting contemporary art in a historical perspective. An examination of the accounting and storage documentation, as  well as the main regulations governing the stock work, allowed to identify the problematic field of the creation and sustenance of a museum collection of contemporary art in the 21st century. The issues related to the museumification of new art forms and trends present both theoretical (the works of media artists often blur the boundaries between the concepts of ‘original’ and  ‘copy’, questioning the idea of the uniqueness of the work), and practical challenges (it is not always clear what should be preserved in case of street art works: a part of the wall with an image, a stencil, or perhaps just photo and video documentation). On the basis of the analysis of several curatorial projects held by the Department of Contemporary Art (“Russian Museum. Gifts and Acquisitions. Section of the Newest Trends”, “Generation of Thirties in Contemporary Russian Art”, etc.), the “exhibition” method of replenishing funds has been emphasized as the most adequate to the task of the replenishment of museum collections of contemporary art.
Keywords: The State Russian Museum; museum and contemporary art; department of contemporary art; contemporary art in the Russian museum; collecting contemporary art; media art in the museum; street art in the museum